Effect of Zr on microstructure and high-temperature mechanical properties of austenitic heat resistant steel. (4th October 2019) - Wang, Shuai; Zheng, Kaihong; Zheng, Zhibin; Wang, Juan; Long, Jun; Li, Yingmin
Abstract: The microhardness and tensile properties of K-52 steel with Zr element has been studied at room temperature, 300 °C, 500 °C and 700 °C, respectively. The results showed that the addition of Zr element improved the microhardness of the steels at different temperature, and the hardening mechanism was detailed evaluated by microstructure and phase analysis methods. The high temperature tensile properties for the test steels were investigated by analyzing the tensile curves and fracture morphology. Compared with K-52 steel, the yield strength and tensile strength of Zr-containing steel increased by 23.53% and 6.73%, respectively. It is also found that the addition of Zr element can improve the size and distribution of inclusions, as well as reduce the sensitivity of the elongation of the steel to temperature at the high temperatures. Between the normal temperature and 500 °C, the ξ values of the Zr-containing steel is 0.47 times that of the matrix steel. However, when the temperature is raised from 500 °C to 700 °C, the ξ values of the Zr-containing steel is only